Integrating futures imaginaries, expectations and anticipatory practices: practitioners of artificial intelligence between now and future - Hautala Johanna; Ahlqvist Toni (Technology Analysis & Strategic Management, Routledge, 2022)
Artiﬁcial intelligence (AI) is a world-changing technology due to its abilities to learn independently, process big data, and automate human work. Imagining the socio-technical future is necessary, but challenging, in the era of AI that rapidly developing technology has made turbulent. In this study, we addressed the need to understand the ways AI practitioners actualise their AI-related futures imaginaries at the grassroots level and in the present. Our empirical case study concerned Finland and Singapore, focussing on their AI strategies based on interviews with 26 AI practitioners. We created a new conceptual perspective by integrating three concepts: futures imaginaries, expectations, and anticipatory practices. We showed that imagining socio-technical futures is an ongoing process in which AI practitioners repeatedly co-constitute the future in ‘the now’. These practitioners interpret futures imaginaries as expectations and address AI-related challenges via anticipatory practices. Whereas some AI practitioners ‘ride the wave’ of the AI hype, others are proactive and critically active in developing and educating people on AI. AI practitioners hold signiﬁcant anticipatory agency that is actualised in the anticipatory zone.